Chapter David Sassoli: Europa, Europa! - Marcheschi, Daniela (Libere carte, 2023)
David Sassoli has best interpreted the great Italian tradition of Europeanism, which had in Giuseppe Mazzini, Vincenzo Gioberti, Altiero Spinelli and Ernesto G. Rossi, the highest and most concrete theoretical and political expressions of the contemporary age. Europe means democracy, therefore freedom, social justice, solidarity among the peoples and within the peoples that make up the European Union. It means building and looking upwards towards peace.